Business risk management programs under review. (10th January 2020) - Slade, Peter
Abstract: The Canadian federal, provincial, and territorial governments recently enacted a new 5‐year agricultural policy framework, the Canadian Agricultural Partnership . While the framework contained few changes to existing policies, the governments also committed to a full review of Canadian business risk management (BRM) programs. In this article, I provide an overview of the existing suite of BRM programs and summarize the BRM program review. I conclude by making recommendations for future policy frameworks. Abstrait: Les gouvernements fédéraux, provinciaux et territoriaux du Canada ont récemment adopté un nouveau cadre stratégique quinquennal pour l'agriculture, le Partenariat agricole canadien. Bien que le cadre contienne peu de changements aux politiques existantes, les gouvernements se sont également engagés à effectuer un examen complet des programmes de la gestion des risques de l'entreprise (GRE). Dans cet article, je donne un aperc̏u du portefolio de programmes de GRE et résume l'examen du programme de GRE. Je conclus en faisant des recommandations pour les futurs cadres politiques.